Neurobehavior and MRI in 22ql3.3 Deletion Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Neuromotor, sensory, language, communication and social development, and cerebral MRI and PET studies were performed in 8 children with 22ql3.3 deletion syndrome, at the National Institutes of Health, Necker-Enfants Malades Hospital, and other centers in Paris, France.